Case report: Autoimmune encephalitis with multiple auto-antibodies with reversible splenial lesion syndrome and bilateral ovarian teratoma - Li, Yaqiang; Zhang, Mei; Liu, Deshun; Wei, Ming; Sheng, Jun; Wang, Zhixin; Xue, Song; Yu, Tingting; Xue, Weimin; Zhu, Beibei; He, Jiale (Frontiers in Immunology, 2023)
Background Reversible splenial lesion syndrome (RESLES) is a spectrum of disease radiologically characterized by reversible lesions caused by multiple factors, primarily involving the splenium of the corpus callosum (SCC). The most common causes of RESLES include infection, antiepileptic drug use and withdrawal, and severe metabolic disorders. Nevertheless, cases of autoimmune encephalitis (AE) are uncommon. Case presentation A 26-year-old female computer programming engineer with no previous medical or psychiatric history reported to the psychiatric hospital due to a 3-day episode of irritability, babbling, limb stiffness, sleepwalking, hallucinations, and paroxysmal mania. Brain MRI revealed abnormal signals of the SCC. Lumbar puncture was performed and further testing for auto-antibodies was conducted in both the CSF and serum. CSF of the patient was positive for anti-NMDAR (titer of 1:3.2) antibodies, and serum was also positive for anti-NMDAR (titer of 1:32) as well as mGluR5 (titer of 1:10) antibodies. Enhanced CT of the pelvis showed an enlarged pelvic mass; bilateral ovarian teratomas (mature teratoma and immature teratoma) were evaluated, which were pathologically confirmed after transabdominal left adnexal resection, right ovarian biopsy, and ovarian cystectomy. The patient considerably improved after intravenous administration of steroids, immunoglobulin, oral prednisone, surgical treatment, and chemotherapy. A follow-up MRI revealed completely resolved lesions. During a 3-month follow-up, the patient experienced complete resolution of symptoms without any sign of recurrence and tumors. The titer of the anti-NMDAR antibody decreased to 1:10 in serum. Conclusion Herein, we report a rare case of AE with overlapping auto-antibodies, along with RESLES and bilateral ovarian teratomas. The current case provides the possibility of the concurrence of mGluR5 antibodies in anti-NMDAR encephalitis. However, the underlying mechanism remains elusive. Furthermore, we provide additional evidence that overlapping antibodies-related pathology may be one of the many causes of RESLES. Nonetheless, caution should be observed in interpreting the observation, considering that this is a single-case study.